THE IMAGE OF RIJEKA IN MILOS CRNJANSKI’S TRAVEL REPORTS (Heritage, 2024)
The paper deals with Miloš Crnjanski's travel reports dedicated to Rijeka, the largest city in the Kvarner Gulf, published during the 20s of the 20th century in Politika. We are talking about Crnjansk's engaging texts that have remained on the margins of scientific and research interest so far.The analysis of the texts showed that Crnjansk's travel reports about Rijeka were not aimed at introducing the readers of Politika to a different culture by highlighting its specificities, nor bringing them closer to Serbian readers with the insufficiently known areas of the newly created Yugoslav state (which was the main goal of author's travel reports from the northern Croatian coast), but primarily expressing his own political views and pointing out the danger of Italy and fascist ideology, which also indicates that the writer used the travelogue genre to realize broader, non-literary ideas.On the other hand, in a formal sense, the writer introduces many characteristics of the travelogue genre, so in the text one encounters the motifs of the road and unknown environment, but also the establishment of a series of mutually conditioned dichotomies, starting with the primary one based on the relationship between us and them. In this regard, we can conclude that "The Murder of Rijeka" genre oscillates between a travel reportage and a political text, and perhaps it would be most accurate to speak of an engaged travel reportage, because all its parts are in the function of constructing political attitudes and creating certain ideological positions.Therefore, bearing in mind the aforementioned travelogue and reportage records, we can conclude that for Miloš Crnjanski, Rijeka is an inspiring place that, on the one hand, has a sentimental value, while, on the other hand, it signifies an important cultural, historical and political segment of the Kingdom of Yugoslavia and its identity.
Keywords: Miloš Crnjanski, Rijeka, travelogue, reportage, engaged literature, Yugoslav national identity